ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„ØªØ¹Ø¨ÙŠØ± Ø§Ù„ÙƒØªØ§Ø¨ÙŠ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø£ÙÙ„Ø§Ù… Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ù‚ØµÙŠØ±Ø© Ø¨Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¯Ø§Ø± Ø§Ù„ØÙƒÙ…Ø© ÙØ±Ø§Ø³ÙˆØº Ø³ÙŠØ¯ÙˆÙˆØ§Ø±Ø¬Ø§ - Nahdly, M. As'ad (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2021)
Ù…Ø³ØªØ®Ù„Øµ Ø§Ù„Ø¨ØØ«: Ø¥Ù† Ø§Ù„ÙƒØªØ§Ø¨Ø© Ø¥ØØ¯Ù‰ Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø£Ø³Ø§Ø³ÙŠØ© ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø£ÙˆÙ„Ù‰ ÙˆØ§Ù„Ù„ØºØ© Ø§Ù„Ø£Ø¬Ù†Ø¨ÙŠØ© Ø¹Ù„Ù‰ ØØ¯ Ø³ÙˆØ§Ø¡. ÙˆØ§Ù„ÙƒØªØ§Ø¨Ø© Ù†Ø´Ø§Ø· Ø°Ù‡Ù†ÙŠ ÙŠØ¹ØªÙ…Ø¯ Ø¹Ù„Ù‰ Ø§Ù„Ø¥Ø®ØªÙŠØ§Ø± Ø§Ù„ÙˆØ§Ø¹ÙŠ Ù„Ù…Ø§ ÙŠØ±ÙŠØ¯ Ø§Ù„ÙØ±Ø¯ Ø§Ù„ØªØ¹Ø¨ÙŠØ± Ø¹Ù†Ù‡ ÙˆØ§Ù„Ù‚Ø¯Ø±Ø© Ø¹Ù„Ù‰ ØªÙ†Ø¸ÙŠÙ… Ø§Ù„Ø®Ø¨Ø±Ø§Øª ÙˆØ¹Ø±Ø¶Ù‡Ø§ Ø¨Ø´ÙƒÙ„ ØªØØ±ÙŠØ±ÙŠ. ÙÙŠ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¯Ø§Ø± Ø§Ù„ØÙƒÙ…Ø© ÙØ±Ø§Ø³ÙˆØº Ø³ÙŠØ¯ÙˆÙˆØ§Ø±Ø¬Ø§ Ø£Ù† Ø§Ù„ÙƒÙØ§ÙŠØ© Ø§Ù„Ø£Ø³Ø§Ø³ÙŠØ© ÙÙŠ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø© Ù‡ÙŠ Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ù„Ø§Ø¨ Ø¹Ù„Ù‰ ÙƒØªØ§Ø¨Ø© Ø§Ù„ÙƒÙ„Ù…Ø© Ø§Ùˆ Ø§Ù„Ø¬Ù…Ù„Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø¹Ù„Ø§Ù…Ø§Øª Ø§Ù„ØªØ±Ù‚ÙŠÙ… Ø§Ù„ØµØÙŠØØ© ÙˆÙ‚Ø¯Ø±ØªÙ‡Ù… Ø¹Ù„Ù‰ ØªØ¹Ø¨ÙŠØ± Ø¹Ù† Ø§Ù„Ø¢Ø±Ø§Ø¡ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„ØªØ±Ø§ÙƒÙŠØ¨ Ø§Ù„ØµØÙŠØØ©. ÙˆÙ‡ÙŠ ØªØ®ØªÙ„Ù Ø¹Ù† Ø§Ù„Ù†ØªØ§Ø¦Ø¬ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„ÙˆØ§Ù‚Ø¹Ø© ÙÙŠ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø© ÙÙŠ Ù…Ø¬Ø§Ù„ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ ÙƒØ«ÙŠØ± Ù…Ù† Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ø®Ø§ØµØ© Ø¨Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¯Ø§Ø± Ø§Ù„ØÙƒÙ…Ø© ÙØ±Ø§Ø³ÙˆØº Ø³ÙŠØ¯ÙˆÙˆØ§Ø±Ø¬Ø§. ÙØ¥Ù† Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ù„Ù… ØªÙƒÙ† ÙØ¹Ø§Ù„Ø© ÙÙŠ ØªØÙ‚ÙŠÙ‚ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø© ØŒ Ø¨Ù…Ø§ Ø¸Ù‡Ø± ÙÙŠ Ø¶Ø¹Ù ÙƒØªØ§Ø¨ØªÙ‡Ù… ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© . Ø³ÙˆÙ‰ Ø°Ø§Ù„Ùƒ ÙƒØ§Ù† Ù…ÙŠÙ„ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„ÙƒØªØ§Ø¨Ø© Ù…Ù†Ø®ÙØ¶Ø© ÙˆÙ„Ø§ ÙŠØ´ØªØ±ÙƒÙˆÙ† ÙÙŠÙ‡Ø§ Ø§Ø´ØªØ±Ø§ÙƒØ§ Ø¬ÙŠØ¯Ø§ . ÙˆØ±Ø£Ù‰ Ø§Ù„Ø¨Ø§ØØ« Ø£Ù† Ø§Ù„Ù…Ø´ÙƒÙ„Ø© Ø§Ù„Ø±Ø¦ÙŠØ³ÙŠØ© Ù‡ÙŠ Ù‚Ù„Ø© Ø§Ø³ØªØ¹Ù…Ø§Ù„ Ø§Ù„Ù…Ø¯Ø±Ø³ Ù„Ù„Ø·Ø±Ø§Ø¦Ù‚ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ù…ØªÙ†ÙˆØ¹Ø© Ø£ÙˆØ§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© . Ù…Ø«Ù„Ø§ Ø£Ù† Ø§Ù„Ù…Ø¯Ø±Ø³ Ø¹Ù„ÙŠ Ø£Ù† Ø§Ù„Ù„ØºØ© ÙˆØ¸ÙŠÙØªÙ‡Ø§ ÙŠØ³ØªØ®Ø¯Ù… Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„Ù…Ù‚Ø±Ø± ÙƒØ«ÙŠØ±Ø§ ÙˆÙ„Ø§ÙŠØ³ØªØ®Ø¯Ù… Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ø£Ø®Ø±Ù‰ØŒ ÙˆÙŠØ³ØªØ®Ø¯Ù… Ø£ÙŠØ¶Ø§ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙÙ‚Ø· Ø«Ù… ÙŠÙƒØªØ¨ Ø§Ù„Ø·Ù„Ø§Ø¨ Ù…Ø§ ÙŠÙ‚Ø±Ø£Ù‡ Ø§Ù„Ù…Ø¯Ø±Ø³ ØØªÙŠ ÙŠØ´Ø¹Ø±ÙˆØ§ Ø¨Ø§Ù„Ù…Ù„Ù„ ÙˆÙ„Ø§ ÙŠØØµÙ„ÙˆØ§ Ø¹Ù„ÙŠ Ø§Ù„Ø£ØºØ±Ø§Ø¶ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ©. Ù„Ø°Ø§Ù„Ùƒ Ø£Ø±Ø§Ø¯ Ø§Ù„Ø¨Ø§ØØ« Ø£Ù† ÙŠÙ‚Ø¯Ù… Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ø£Ø®Ø±Ù‰ Ù„ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„ØªØ¹Ø¨ÙŠØ± Ø§Ù„ÙƒØªØ§Ø¨ÙŠ Ù„Ù„Ø·Ù„Ø§Ø¨ ÙˆÙ‡ÙŠ Ø§Ù„Ø£ÙÙ„Ø§Ù… Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ù‚ØµÙŠØ±Ø©. ÙˆÙŠØªØ±ÙƒØ² Ø§Ù„Ø¨Ø§ØØ« Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ØªØ¹Ø¨ÙŠØ± Ø§Ù„ÙƒØªØ§Ø¨ÙŠ Ø¨Ù†Ø¸Ø±ÙŠØ© Ø§Ù„Ø¥ØªØµØ§Ù„ Ø§Ù„Ø°ÙŠ Ù‡Ùˆ Ø§Ù„Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªÙŠ ÙŠØªÙØ§Ø¹Ù„ Ø¨Ù…Ù‚ØªØ¶Ø§ÙŠØªÙ‡Ø§ Ù…ØªÙ„Ù‚ÙŠ ÙˆÙ…Ø±Ø³Ù„ Ø§Ù„Ø±Ø³Ø§Ù„Ø© ÙÙŠ Ù…Ø¶Ø§Ù…ÙŠÙ† Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© Ù…ØØ¯Ø¯Ø© ÙˆÙ‡Ø° Ø§Ù„ØªØ¹Ø±ÙŠÙ ÙŠØ¸Ù‡Ø± Ø£Ù† Ø£Ù† Ø§Ù„Ø¥ØªØµØ§Ù„ Ù‡Ù†Ø§ ÙŠÙ‚ÙˆÙ… Ø¹Ù„ÙŠ Ù…Ø´Ø§Ø±ÙƒØ© Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª ÙˆØ§Ù„ØµÙˆØ± Ø§Ù„Ø°Ù‡Ù†ÙŠØ© ÙˆÙ‡Ø°Ø§ Ø§Ù„Ø¹Ù†ØµØ± Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ Ù…Ù‡Ù… ÙÙŠ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø¹Ø±Ø¨ÙŠ ÙˆØªØ¯Ù„ Ù‡Ø°Ù‡ Ø§Ù„Ù†Ø¸Ø±ÙŠØ© Ø§Ù„Ø§ØªØµØ§Ù„ÙŠØ© Ù„Ø§ ØªØ®Ø±Ø¬ Ù…Ù† Ø§Ù„ØºØ±Ø¶ Ø§Ù„ØªØ±Ø¨ÙˆÙŠ Ø§Ù„Ø°ÙŠ Ù‡Ùˆ Ù†Ù‚Ù„ Ø§Ù„Ù‚ÙŠÙ… Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ø§Ù† Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø© Ø¨Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¯Ø§Ø± Ø§Ù„ØÙƒÙ…Ø© ÙØ±Ø§Ø³ÙˆØº Ø³ÙŠØ¯ÙˆÙˆØ§Ø±Ø¬Ø§ ØŒ Ø¨Ø¹Ø¯ Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø£ÙÙ„Ø§Ù… Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ù‚ØµÙŠØ±Ø© ØªÙ†Ù…Ùˆ Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„ØªØ¹Ø¨ÙŠØ± Ø§Ù„ÙƒØªØ§Ø¨ÙŠ Ø¨Ø§Ø¹ØªÙ…Ø§Ø¯ Ù„Ù„Ø¥ØªØµØ§Ù„ ÙˆÙ…Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ù„Ø¨Ø© Ø§Ù„Ø¥ØªØµØ§Ù„ÙŠØ© ÙƒØ§Ù†Øª ØªÙ†Ù…ÙŠØªÙ‡Ø§ Ø§Ù„ÙØ¹Ø§Ù„Ø© Ù‡ÙŠ Ø§ÙƒØªØ³Ø§Ø¨ Ø§Ù„Ù„ØºØ© Ù…Ø¨Ø§Ø´Ø±Ø© Ù…Ù† Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ù‡Ø§ Ø¨Ø§Ù„Ø£ÙÙ„Ø§Ù… Ø§Ù„ØªÙŠ ØªØ¹Ø¨Ø± Ø¹Ù† Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª ÙˆØ§Ù„Ø£Ø±Ø§Ø¡ ÙˆØ§Ù„ØµÙˆØ± Ø§Ù„ØªÙŠ Ù„Ù‡Ø§ Ø³ÙƒÙˆÙ„ÙˆØ¬ÙŠØªÙ‡Ø§ ÙˆØ«Ù‚Ø§ÙØªÙ‡Ø§ Ø§Ù„Ø¥Ø¬ØªÙ…Ø§Ø¹ÙŠØ© ÙƒÙ…Ø§ ÙƒØ§Ù†Øª Ø§Ù„Ù†Ø¸Ø±ÙŠØ© Ø§Ù„Ù…Ù†Ø§Ø³Ø¨Ø© Ø¨Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ø§Ù„Ù†Ø¸Ø±ÙŠØ© Ø§Ù„Ø¥ØªØµØ§Ù„ÙŠØ© Ø§Ù„ØªÙŠ ØªÙ…Ù†Ø¹ Ø§Ù„Ø·Ø§Ù„Ø¨ Ø£Ù† ÙŠØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø¥Ù„Ø§ ÙˆÙ‡Ùˆ Ù†Ø§Ø·Ù‚ Ø¨Ù‡Ø§. Ø§Ù„ÙƒÙ„Ù…Ø© Ø§Ù„Ù…ÙØªØ§ØÙŠØ© : ØªÙ†Ù…ÙŠØ©, Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„ÙƒØªØ§Ø¨ÙŠ, Ø§Ù„Ø£ÙÙ„Ø§Ù… Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ù‚ØµÙŠØ±Ø© Abstrack Writing is one of the essential skills in learning both a first language and a foreign language. Writing is a mental activity that depends on the conscious choice of what the individual wants to express and the ability to organize experiences and present them in writing. In the Islamic Islamic Boarding School of Darul Hikmah Prasung Sidoarjo, the basic competence in writing skill is the ability of students to write a word or sentence using correct punctuation marks and their ability to express opinions using correct structures. It differs from the educational results in the skill of writing in the field of teaching the Arabic language in many Islamic schools, especially in the Islamic Boarding School of Darul Hikmah Prasung Sidoarjo. The teaching process was not effective in achieving the skill of writing, as shown by the weakness of their writing in the Arabic language. Otherwise, the students' tendency to teach writing was low and did not share it well. The researcher considered that the main problem is the teachers â€™lack of use of various educational methods or teaching aids. For example, the teacher uses the textbook a lot and does not use the other method, and also uses the reading method only, and then students write what the teacher reads until they are bored and do not get the educational purposes. Therefore, the researcher wanted to provide the other educational means to develop students' written expression skills, which is short educational films. The researcher concentrates the skill of written expression in the theory of communication, which is the process whereby the recipient and the sender of the message interact in specific social contexts, and this definition shows that communication here is based on the sharing of information and mental images and this social element is important in Arab education and indicates this communication theory does not depart from the educational purpose that It is the transmission of religious social values The writing skill at the Islamic Boarding School of Darul Hikmah Prasung, after the use of short educational films, the written expression skills grow depending on the fact that the language is its function for communication and the ability of students to communicate effectively, its effective development is to acquire the language directly from its speakers through films that express information, opinions and images that have its own science and culture. The social theory and the appropriate theory in this research is the communicative theory that prevents the student from learning the language without speaking it. Keyword: development, writing skills, short educational films.